Preliminary Study of Genially Educational Games for Collaboration on Business and Energy Materials - Aprilia Wulandari; M. Hidayat; Erlida Amnie (Master of Physics Education Study Programme, 2026)
This preliminary study explores the potential of Genially-based educational games to enhance students’ collaboration skills in physics, specifically in the work-and-energy unit. A mixed-methods approach was used, collecting data through teacher interviews and a Likert-scale questionnaire administered to 27 ninth-grade students at SMP Adhyaksa 1 Jambi. Results show students' conceptual understanding is good (mean 3.67), although 85.2% still find abstract concepts challenging. Teachers' media use remains limited, while students view educational games as beneficial, especially when accompanied by brief explanations and practice questions. Collaboration skills are rated good to very good (mean 3.95), particularly in respecting opinions and accepting suggestions. These findings suggest Genially-based educational games have significant potential as innovative learning media that support conceptual understanding and foster collaboration skills aligned with 21st-century educational goals.